Effects of local structure on helium bubble growth in bulk and at grain boundaries of bcc iron: A molecular dynamics study. (15th September 2015) - Yang, L.; Gao, F.; Kurtz, R.J.; Zu, X.T.; Peng, S.M.; Long, X.G.; Zhou, X.S.
Graphical abstract: Abstract: The nucleation and growth of helium (He) bubbles in the bulk and at Σ3〈1 1 0〉1 1 2 and Σ73b〈1 1 0〉6 6 1 grain boundaries (GBs) in bcc iron have been investigated using molecular dynamics simulations. The results show that a 1/2〈1 1 1〉1 1 1 dislocation loop is formed with the sequential collection of 〈1 1 1〉 interstitial crowdions at the periphery of the He cluster and is eventually emitted from the He cluster. Insertion of 45 He atoms into a He cluster leads to the formation of a 1/2〈1 1 1〉 dislocation loop in Σ3 GB. It is of interest to notice that the transition of a dislocation segment through the GB leads to the formation of a step at the GB plane following the loop formation, accounting for the formation of a residual GB defect. A 1/2〈1 1 1〉 loop, with a 1 1 0 habit plane, is emitted with further increase of the He bubble size in the Σ3 GB. In contrast, the sequential insertion of He atoms in Σ73b GB continuously emits self-interstitial atoms (SIAs), but these SIAs rearrange at the core of the inherent GB dislocation, instead of forming a dislocation loop, which leads the GB dislocation to propagate along the [ 1 ¯ 1 ¯ 1 2 ] direction. In the bulk and Σ3 GB, the He bubble exhibits three-dimensionally spherical shape, but it forms longitudinal shape along the dislocation line in the Σ73 GB, a shape commonly observed at GBs in experiments.